The illustrations of the conflict between Israel and Hamas in the Greek Cypriot press : the case of o Phileleftheros tis Kyriakis - Antoniades, Euripides (My University, 2025)
On October 7, 2023, the conflict between Hamas-led Palestinian organisations and Israel commenced when armed Palestinian terrorists invaded Israeli territory, marking the most significant act of terrorism since the establishment of the State of Israel. A day later, the Israeli counterattack began, with constant bombardments and a total blockade of the Gaza Strip, as well as clashes in the West Bank and on Israel‘s border with Lebanon. At the same time, there were many demonstrations around the world against the Hamas-Israel war, while the UN warned that there is a serious risk of genocide in Gaza. The United Nations and various human rights groups have highlighted that Hamas is guilty of war crimes for targeting civilians and taking hostages during the October 7 invasion. Israel has also been accused of war crimes for imposing collective punishment on Palestinians through civilian deaths, forced evacuations from Gaza City, and the use of bombs. This paper studies how the Sunday Greek Cypriot press reports on the war crisis between Israel and Hamas from the beginning of the crisis until the end of May 2024. Our aim is to highlight the importance of printed press as a vital source of information for the Cypriot public, particularly in relation to the crisis occurring in close proximity to Cyprus where the armed conflicts are taking place. The year 1974 marked a significant period of conflict in Cyprus, and its consequences continue to be observed today. Through content analysis, this study aims to examine the overall role of the press during conflicts and draw conclusions accordingly. Newspapers, in addition to being objects of research and study, will be used as historical sources for the period in question. More specifically, the paper focuses on the Greek Cypriot newspaper O Phileleftheros tis Kyriakis (English translation: The Sunday Liberal) and attempts to present its political positions in relation to the conflict landscape in the neighboring region of Cyprus.
Keywords: press; Cyprus; Hamas; Israel; conflicts